Replication Report: Checking and Sharing Alt-Facts - Monica Beeder; Erik Ø. Sørensen (Institute for Replication (I4R), 2023)
Henry, Zhuravskaya, and Guriev (2022) examine whether people are willing to share "alternative facts" espoused by right-wing populist parties before the 2019 European elections in France and how this interacted with the availability of fact-checking information. They find that both imposed and voluntary fact-checking reduce the likelihood of sharing false statements by approximately 45%, and that imposed and voluntary fact-checking have similar effect sizes. We reproduce these findings and introduce several alternative estimates to assess the robustness of the original results, including resolving an inconsistency in the handling of pre-treatment controls. Overall, our results align with the results of the original paper. The differences we find are small in absolute magnitude but, since many effects were small, not always trivial in terms of relative differences. This replication supports the conclusions of the original paper.
Keywords: 330; Replication; Fake News; Alternative facts